2004
DOI: 10.1074/jbc.m400881200
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Membrane-associated Sialidase MmNEU3 Modifies the Ganglioside Pattern of Adjacent Cells Supporting Its Involvement in Cell-to-Cell Interactions

Abstract: We describe herein the enzyme behavior of MmNEU3, the plasma membrane-associated sialidase from mouse (Mus musculus). MmNEU3 is localized at the plasma membrane as demonstrated directly by confocal microscopy analysis. In addition, administration of the radiolabeled ganglioside GD1a to MmNEU3-transfected cells, under conditions that prevent lysosomal activity, led to its hydrolysis into ganglioside GM1, further indicating the plasma membrane topology of MmNEU3. Metabolic labeling with [1-3 H]sphingosine allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 61 publications
9
144
0
2
Order By: Relevance
“…An important point is to demonstrate that the plasma membrane associated activities were conserved in living cells. For Neu3 sialidase we have already demonstrated its activity on glycoconjugates located at the cell surface of neighboring cells [13]. To look for b-galactosidase and b-glucosidase activities in living cells, we used both artificial and natural substrates as described in Section 2.…”
Section: Resultsmentioning
confidence: 99%
“…An important point is to demonstrate that the plasma membrane associated activities were conserved in living cells. For Neu3 sialidase we have already demonstrated its activity on glycoconjugates located at the cell surface of neighboring cells [13]. To look for b-galactosidase and b-glucosidase activities in living cells, we used both artificial and natural substrates as described in Section 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, an additional level of regulation of glycosphingolipid expression has been recently suggested to occur at the plasma membrane level, with the existence being reported of a plasma membrane-associated sialidase, termed Neu3, which is able to trigger selective ganglioside desialylation in different cell types (17)(18)(19). Moreover, ␤-hexosaminidase (20), ␤-glucosidase, and ␤-galactosidase (21) activities have also been demonstrated at the cell surface, suggesting their role in the remodeling of the plasma membrane glycosphingolipids, thus contributing to modulate lipid composition and membrane organization, and consequently, different signaling processes (21,22).…”
mentioning
confidence: 99%
“…These lipids play key role as signaling molecules in both physiological and pathological processes regulating cell-to-cell and/or cell-environment interactions [3,38]. Several recent studies revealed the presence of glycohydrolases not only in lysosomes but also at cell surface [5,18,39,40]. They stress the potential role of a remodelling of glycosphingolipids during cellular processes [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, new studies show the presence of glycohydrolases at the plasma membrane (PM) and point to their potential role in modifying glycosphingolipids during signaling and cellular communication [3,4]. For instance, evidence for PM sialidase Neu3 activity towards gangliosides exposed to the surface of adjacent cells has been recently demonstrated by co-culture experiments [5,6]. Moreover, the presence of the lysosomal sialidase Neu1 anchored to both lysosomal and plasma membranes has been established and an important immunoregulatory role for this enzyme has been suggested [7,8].…”
Section: Introductionmentioning
confidence: 99%